Fibroblast Growth Factor-Inducible 14: Multiple Roles in Tumor Metastasis - Wang, X.; Zeng, Y.; N. Ho, D.; Yin, J.; Liu, G.; Chen, X. (Current Molecular Medicine, 2015)
Metastasis, the main cause of mortality in cancer patients, is a complex process consisting of several sequential, interlinked, and highly-selective steps. Fibroblast growth factor-inducible 14 (Fn14) is one member of the tumor necrosis factor receptor family, which is influential in controlling cell division, life, and death. The role of Fn14 in tumor metastasis regulation is slowly being unraveled, including roles in the regulation of the epithelial-mesenchymal transition, angiogenesis, cytoskeleton modulation, extracellular matrix degradation and inflammation. This review will focus on recent studies that demonstrate the involvement of Fn14 in tumor progression and will briefly describe various pathways of Fn14-regulated metastasis. Finally, future prospects will be discussed for the potential role of Fn14 as a predictive marker and therapeutic agent for tumor metastasis suppression.
Keywords: Fn14